METHODS OF DEVELOPING GENERAL COMPETENCES OF FUTURE TEACHERS IN THE PROCESS OF USING MUSEUM RESOURCES - Murodova Durdonakhon Kamoliddinovna (Modern American Journals, 2025)
This article discusses the scientific methods of developing general cultural competencies in future teachers through the use of museum resources. General cultural competence forms a person's skills such as understanding cultural heritage, aesthetic taste, respect for spiritual values, entering into cultural dialogue, and accepting universal human values. The article analyzes the theoretical foundations of museum pedagogy, methods of using museum resources in the educational process, interactive approaches, project-based learning, and the possibilities of using digital museum technologies. Based on foreign and national experience, the educational potential of museum resources is shown and recommendations for their use in the pedagogical process are developed.
Keywords: Museum resources, general cultural competence, future teachers, museum pedagogy, interactive methods, project-based learning, digital museum.